2000
DOI: 10.1074/jbc.m004462200
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Membrane-bound Ribosomes Following the Termination of Protein Synthesis

Abstract: Contemporary models for protein translocation in the mammalian endoplasmic reticulum (ER) identify the termination of protein synthesis as the signal for ribosome release from the ER membrane. We have utilized morphometric and biochemical methods to assess directly the fate of membrane-bound ribosomes following the termination of protein synthesis. In these studies, tissue culture cells were treated with cycloheximide to inhibit elongation, with pactamycin to inhibit initiation, or with puromycin to induce pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 29 publications
10
70
0
1
Order By: Relevance
“…Also, the increase in P basal produced by both PUR and PAC was about 70% of the ⌬P PUR measured in control cells (Fig. 4, A and B, where ⌬P PUR reflects the size of the translationally active pool in control cells), which was remarkably consistent with the previous report of a persistent binding of Ϸ65% of 60 S subunits after the release of nascent proteins (5).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Also, the increase in P basal produced by both PUR and PAC was about 70% of the ⌬P PUR measured in control cells (Fig. 4, A and B, where ⌬P PUR reflects the size of the translationally active pool in control cells), which was remarkably consistent with the previous report of a persistent binding of Ϸ65% of 60 S subunits after the release of nascent proteins (5).…”
Section: Resultssupporting
confidence: 80%
“…The increased permeability to 4-M␣G was consistent with a previous report that RBTs incorporated into planar bilayers and opened by puromycin are permeable to ions (3), and our results were also supported by a recent report that puromycin can release calcium from the RER (4). The permeation of empty RBTs is especially significant in the context of recent studies by Nicchitta and colleagues (5,6), who reported that approximately two-thirds of the 60 S subunits remain bound to translocons after the normal completion of protein translation, thereby constituting a large pool of persistent, translationally inactive RBT complexes. Although permeation of these empty RBTs could have very important consequences for RER-dependent signaling and the maintenance of essential gradients across the RER membrane, this pathway has received relatively little attention.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…3, D and E), indicating that agonist-stimulated iNOS activation is independent of changes in the levels of iNOS protein expression. As a further support to this conclusion, we also obtained data that preincubation with a protein synthesis inhibitor puromycin under conditions shown previously to abolish protein translation (22,23) did not affect the thrombin-induced NO production in wild-type or eNOS knock-out platelets (data not shown). Consistent with these results, we have also obtained data that there is no significant de novo synthesis of Bcl-3, a protein shown to be synthesized after prolonged platelet activation, after 5 min of agonist stimulation of mouse platelets under the same experimental conditions that iNOSdependent NO synthesis was demonstrated (data not shown).…”
Section: Role Of Inos In Agonist-induced Platelet No Production-tosupporting
confidence: 67%
“…This technique has been previously used to successfully fractionate cytosolic mRNAs from ER-bound mRNAs [23].…”
Section: Glucose Stimulates the Selective Recruitment Of Proinsulin Mmentioning
confidence: 99%